Application of Time Study Model in Rice Milling Firm: A Case Study - AO Odior; FA Oyawale (Journal of Applied Sciences and Environmental Management)
This paper presents a case study in the development and application of a time study model in a rice milling firm. Rice milling is a process whereby the rice grain is transformed into a form suitable for human consumption and it has to be done with utmost care to prevent breakage of the kernel and improve the recovery. Rice is a very important nutritional diet for over half the world's population and as a result rice milling firm has occupied a significant position in small, medium and large scale enterprises of many nations. The study reveals that the time it takes to mill a 50 kilograms bag of rice is directly proportional to the number of production stages involved and the time spent at each of these production stages. This time is being represented by some structural equations which are characteristics of the rice milling firm being studied. @JASEM